2019
DOI: 10.3390/d11110218
|View full text |Cite
|
Sign up to set email alerts
|

Dactylonectria and Ilyonectria Species Causing Black Foot Disease of Andean Blackberry (Rubus Glaucus Benth) in Ecuador

Abstract: Andean blackberry (Rubus glaucus Benth) plants from the provinces of Tungurahua and Bolivar (Ecuador) started showing symptoms of black foot disease since 2010. Wilted plants were sampled in both provinces from 2014 to 2017, and fungal isolates were obtained from tissues surrounding necrotic lesions in the cortex of the roots and crown. Based on morphological characteristics and DNA sequencing of histone 3 and the translation elongation factor 1α gene, isolates were identified as one of seven species, Ilyonect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Mora-Sala et al 5 also reported the occurrence of species belonging to the genera Cylindrodendrum, Dactylonectria and Ilyonectria associated with seedlings of diverse hosts showing decline symptoms in forest nurseries in Spain. Sánchez et al 6 showed that Dactylonectria and Ilyonectria species cause black foot disease in Andean blackberry. Moreover, Cylindrocarpon root rot may be responsible for losses up to 30% on ginseng ( Panax quinquefolium ) 7 and plays an important role in black foot rot of grapevines 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Mora-Sala et al 5 also reported the occurrence of species belonging to the genera Cylindrodendrum, Dactylonectria and Ilyonectria associated with seedlings of diverse hosts showing decline symptoms in forest nurseries in Spain. Sánchez et al 6 showed that Dactylonectria and Ilyonectria species cause black foot disease in Andean blackberry. Moreover, Cylindrocarpon root rot may be responsible for losses up to 30% on ginseng ( Panax quinquefolium ) 7 and plays an important role in black foot rot of grapevines 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The blackberries are badly affected by black foot disease, an important disease in producing areas, which was found to be caused by the fungus Dactylonectria torresensis 78 . The antagonistic capacity of isolates of Trichoderma spp.…”
Section: Many Products Consist Of a Single Species Ofmentioning
confidence: 99%
“…In a further trial, on the productivity (yield and weight of the fruit) of the blackberry crop the application of T. asperellum (1.53 x 10 9 CFU/g) produced an increase in yield between 13% and 29% compared to the control. Application of the fungus resulted in larger berries with an increase of 1 g/berry in the treatments where the beneficial fungus was applied 78,50 . During the trials, is was con-firmed that, with periodic (monthly) inoculations of Trichoderma sp.…”
Section: Many Products Consist Of a Single Species Ofmentioning
confidence: 99%
“…For example, Tewoldemedhin et al (2011) reported that these species, specifically C. destructans, caused lesion development on various seedling roots. C. destructans, which was later classified as a new genus called Ilyonectria [22], may either cause a rotting root or trigger a "rusty" root in plants [23]. While the rotting root is a result of a complete invasion of plants by the pathogen through the excretion of fungal enzymes, the "rusty" root is a defense mechanism employed by plants by producing iron phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%